TINGKAT KEPUASAN KONSUMEN Di RESTORAN MCDONALD’S MANADO - Giofany Rondonuwu; Gene H.M. Kapoantow; Charles Ngangi; Eyverson Ruauw (COCOS, 2014)
ABSTRACTGiofany Rondonuwu. The level of Consumer Satisfaction in McDonald's Restaurant Manado, (under the guidance of G.H.M.Kapantow as chairman, Charles R. Ngangi and Eyverson Ruauw as members ).In Manado, there are several kinds of fast food restaurants, one of which is McDonald's. One of the key features to maintain fast food restaurant is costumer satisfaction. Consumer satisfaction is mainly determined by the quality of products and services. The dimensions that influence in shaping the quality of products and services are reliability, responsiveness, assurance, empathy and tangibles. This study aims to determine the level of customer satisfaction for products and services of McDonald 's Restaurant Manado.This study was conducted from September to October 2013 .The population in this study were those who bought and dined in the Restaurant. Sample of 50 respondents were drawn using systematic random sampling method.The results showed that the level of customer satisfaction for products and services in terms of reliability, responsiveness, assurance, empathy isin the more then satisfied category, while tangible is in the satisfie category. The management of McDonald's Restaurant Manado needs to maintain the elements that have been considered good by customer and fixed the things that are considered unsatisfaction by costumers